Older people readmitted to hospital for acute medical care – Implications for occupational therapy. (4th March 2017) - Jönsson, Marie; Appelros, Peter; Fredriksson, Carin
Abstract: Objective: To compare ADL, cognitive function, risk of pressure sores, malnutrition and falls in older people readmitted to hospital. Methods: This was a comparative study. Persons ≥ 75 years, who were readmitted to hospital, were assessed using the ADL-taxonomy and the Mini Mental State Examination. Risks of pressure sores, malnutrition and falls were assessed using Risk Assessment Pressure Sores, Short-Form Mini Nutritional Assessment and Downton Fall Risk Index. Data for comparison for ADL were obtained from an earlier study and risk assessments from a national quality register. Results: Sixty persons were included whose median age was 84 years. The patients had a median of four diagnoses. The mean hospital stay was five days. Most patients were independent in food intake. There was a high degree of dependency in other ADL activities. Nineteen out of 48 patients had 24 point or lower in MMSE. Compared to an age-matched sample, these patients showed a higher risk of pressure sores, risk of falls and dependency in ADL. Conclusion: There is of importance to assess ADL, cognition, risk of falls and pressure sores to determine the needs of older people who are admitted to hospitals. Such assessments, and necessary interventions taken, may prevent unnecessary readmissions.